Pengaruh Religiusitas, Citra Merek dan Bauran Pemasaran terhadap Minat Beli Produk Kecantikan Wardah : (Studi pada Masyarakat Kota Probolinggo) : The Influence of Religiosity, Brand Image and Marketing Mix on Purchase Interest of Wardah Beauty Products: (A Study on the Community of Probolinggo City) - Pratama, Rensia Yuliati; Yuliati, Lilis; Susanto, Arnis Budi (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2023)
The research was aims to determine the influence of religiosity, brand image and marketing mix on the buying interest of Wardah beauty cosmetics. The sample of this research is amounted to 100 respondents who were female of Probolinggo’s society, aged 15 to 67 years and had purchased Wardah beauty products. The analytical tool used in this research is multiple linear regression, using the SPSS 26 program with the value of research variables using a Likert scale. The results of this study indicate that religiosity has no significant on the buying interest of Wardah beauty cosmetics, while brand image and the marketing mix have significant on the buying interest of Wardah beauty cosmetics. The implications of this research can provide an overview regarding interest in buying Wardah beauty products is buying interest of Wardah cosmetics on Probolinggo not based on the religiosity because every consumer has different level of religiosity.